ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb) DI AIR DAN SEDIMEN PADA ALIRAN SUNGAI PERCUT PROVINSI SUMATERA UTARA (Analysis Heavy Metal Lead (Pb) Content in water and sediment in Percut River, North Sumatera) - Irfan Al Husainy; Darma Bakti; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
The river is one of the old used by man for a variety of activities in life, with the decline in the quality of human needs and river due to the presence of one of the various waste pollution accidents are heavy metals. This research aims to analyze the content of Pb and water quality standards based on raw fachir PP No 82 of 2001 by using the method tsoret and determine any metal Pb in sediment and ascertaining the quality of sediment based on raw IACD / CEDA. This research was carried out in November-Desember, 2013.The sample using methods purposive sampling by observing three stations. Parameters observed fisika-kimia waters, is the parameter pb on heavy metal concentration and sediments using atomic there water absorption spectrophotometry ( AAS). The level of heavy metals are on board in the highest station of a 0,08 mg / l based by Government Regulation no. 82 of 2001 and the quality of being inducted into a second. Calamity tackling in the metals concentration is found in sedimentary highest station of 2.7 mg / kg, based on environmnetal quality standars iacd / ceda and still classified as low, the sediment yet exceeding quality standards.Keyword : Storet Method and level of pollution Pb in water, sediment, Percut River